Analisis kimia kualitas air minum dalam perspektif Al-qur’an: Studi pengaruh pencemaran lingkungan terhadap mutu air - Izzatillah, Fina (Maliki Interdisciplinary Journal, 2025)
Clean and safe drinking water is a basic human need and an essential factor in maintaining health and sustainting life. Over the past few decades, the quality of drinking water in various regions has experienced a significant decline. This condition cannot be separted from the increasing intensity of human activities that directly impact the environment, particularly water pollution. This paper aims to discuss drinking water quality from the perspective of chemical parameters and to relate it to the Qur’anic view on human responsibility toward the environment. This study is compiled from several academic journals by lecturers of UIN Malang and other relevant supporting sources. The results indicate that water pollution contributes to increased concentration of certain chemical substances, such as fluoride, nitrate, and heavy metals, wich have the potential to endanger human health. From the Qur’anic perspective, water pollution is understood as a from of corruption or damage (fasād) that contradicts the principle of balance (mīzān) and humanity’s trust and responsibility as khalifah (stewards) on Earth. Therefore, efforts to maintain drinking water quality must be carried out in an integrated manner through scientific approaches and ethical-religious awareness.